Treatment outcome of tuberculosis in children and its associated factors in east coast of malaysia. - Adam, Farzaana (2012)
In 2010, there were 19,337 cases of tuberculosis notified with incidence rate of 66.9 per 100,000 population of which 443 (2.3%) were children. Among factors identified that contributed toward treatment outcome of tuberculosis in children were difficulty in diagnosis and ensuring compliance. This study was conducted to determine the treatment outcome of tuberculosis in children for East Coast of Malaysia and identify factors associated with the treatment outcome. A cross sectional study was conducted through review of medical reports from 2009 through 2011 of children less than 15 years old at eight selected hospitals situated in the states of Kelantan, Terengganu and Pahang. Children who did not complete the treatment by the end of the study period were excluded. Successful treatment outcome was defined as cured and completed treatment. Unsuccessful treatment outcome was defined as cases that defaulted, failed treatment or died. There were 93 children diagnosed and treated as tuberculosis of which 53 (57.0%) were from 5 to 14 years of age, 51 (54.8%) were female, 74 (79.6%) were Malay and 30 (32.3%) came from families with monthly household income of less than R.M800. There were 64 (68.8%) with pulmonary tuberculosis, 23 (24.7%) with weight for age less than the 3rd centile, 25 (26.9%) with comorbidities, 49 (52.7%) with contact to tuberculous patient. There were 67 (72.0%) children which completed treatment, 9 (9.7%) cured, 11(11.8%) defaulted, 1 (1.1%) failed treatment and 5 (5.4%) died. These led to 76 (81.7%) with successful treatment outcome and 17 (18.3%) with unsuccessful treatment outcome. Through multiple logistic regression analysis, non Malay race (odds ratio: 5.84; 95% confidence interval: 1.59, 21.49; p = 0.008) and monthly household income of less than RM800 (odds ratio:6.98; 95% confidence interval: 1.85, 26.28; p = 0.004) were factors found to have significant association with unsuccessful treatment outcome. The main factors associated with unsuccessful treatment outcome identified were low household income and Orang Asli as they comprised of 14 (73.7%) of the non-Malay race.